Usulan Tata Letak Pada Gudang Sparepart dengan Kebijakan Class Based Storage Berdasarkan Analisis ABC di PT. XYZ - Tsany Farras Novrianto; Deny Andesta; Moh. Jufriyanto (Universitas Islam Raden Rahmat, Malang, 2024)
As technology develops, demand increases, and the need for production increases, the layout of factory facilities must be evaluated. PT XYZ is a company that focuses on the production of the most comprehensive fertiliser. Therefore, warehouses are needed in large factory areas and well-designed factory facilities to improve performance and customer satisfaction. The purpose of this study is to propose a warehouse facility layout to mnimize material handling distance. To solve this placement problem, this study uses the classbased storage method based on ABC analysis. After making a proposal by changing a little storage area and grouping materials into classes, the ABC classification results obtained were 13 materials for class A, 2 materials for class B and 1 material for class C, and obtained a total displacement distance in the existing layout of 603.2 m and the proposed layout of 529.2 m, a decrease in total distance of 74 m.